ANALISIS STRATEGI PEMASARAN DAN KEPUASAN KONSUMEN TERHADAP SAYURAN DATARAN TINGGI DI BANDA ACEH - Nurita Puri; Romano Romano; Zakiah Zakiah (Jurnal Bisnis Tani, 2017)
The purpose of this research is to know how highland vegetable marketing strategy in Banda Aceh market and influence of vegetable attribute to consumer satisfaction to highland vegetables in Banda Aceh market. The research sites were conducted in the city of Banda Aceh and located in markets in Banda Aceh such as Peunayong market, Ulee Kareng market and Setui market Banda Aceh City. The population determination was done by Purposive with random sampling on consumer samples. While the traders conducted by survey. The analysis model used is SWOT analysis and multiple linear regression. The strategy of marketing highland vegetables in Banda Aceh market shows that the marketing position of highland vegetable market in Banda Aceh City is on the first awareness of aggressive strategy. the strategy suggested to highland vegetable traders in Kota Banda Aceh is an aggressive strategy. This aggressive strategy illustrates that the marketing efforts of highland vegetables in Banda Aceh City are strong and likely. This means that the organization is in good condition and steady so it is possible for teurs to expand, enlarge growth and maximum growth. While the influence of vegetable attributes on consumer satisfaction on potato vegetables are the attributes of freshness, hygiene, color and potato prices affect the consumer satisfaction, for cabbage vegetables attributes of perfection, freshness, cleanliness, color and price of cabbage affect the consumer satisfaction, as well as on carrot vegetables attributes of perfection , freshness, cleanliness and price influence on customer satisfaction